2020
DOI: 10.1111/cas.14700
|View full text |Cite
|
Sign up to set email alerts
|

Differential glycosylation of collagen modulates lung cancer stem cell subsets through β1 integrin‐mediated interactions

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…In this study, CLDN4 showed approximately 40% of the affinity of CLDN7 for integrin β1. Integrin β1 is known to promote stemness through downstream FAK activation [ 34 , 35 ]. Alterations in the association of cancer cells with the stroma [ 36 ] and Notch signaling have been reported as the underlying mechanisms [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, CLDN4 showed approximately 40% of the affinity of CLDN7 for integrin β1. Integrin β1 is known to promote stemness through downstream FAK activation [ 34 , 35 ]. Alterations in the association of cancer cells with the stroma [ 36 ] and Notch signaling have been reported as the underlying mechanisms [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…It can physically shield CSCs from therapeutic agents and modulate CSCs [ 160 ]. Integrins are prominent ECM surface receptor proteins that mediate cell-to-cell interactions and communication with the ECM [ 161 ], which are critical for the function of CSC [ 162 , 163 ]. The role of integrin depends a lot on lipid raft to transmit signals.…”
Section: Csc Niche and Lipid Raftmentioning
confidence: 99%
“…CD133 is encoded by PROM1 gene composed of 8 N-linked glycosylation sites (93), and the glycosylation plays important roles in maintaining CSC properties (94,95). In fact, glycosylation of CD133 has been suggested as a secondary indicator of CSCs (96)(97)(98). In particular, sialylation of CD133 N-glycan terminal via a2,3-site was found in the CSC of glioma (54), which was augmented in hypoxic conditions, correlating with the migration and survival of brain CSCs (99).…”
Section: Glycosylation Of Csc Markersmentioning
confidence: 99%